Optimization of the Intelligence Network by Unit IV of the State Security Intelligence Unit in Preventing Conflicts Between Pencak Silat Organizations in the Karanganyar Police Jurisdiction - Hertasmara, Alfreza Cahya (Advances in Police Science Research Journal, 2024)
This research is motivated by the phenomenon in the field that conflicts between martial arts organizations in the Karanganyar Police Legal Area occur very often. In the conflict between martial arts colleges, it resulted in many losses, both property and casualties. Therefore, in an effort to create a conducive situation, it is necessary to prevent conflicts between martial arts organizations through efforts to optimize the intelligence network carried out by intelligence unit Karanganyar Police. As an analysis knife, this research uses conceptual literature in the form of theories and / or concepts including: management, Role theory, optimization concepts, basic intelligence concepts. The research approach used is qualitative with a case study research method. Sources of information are obtained from primary data sources and secondary sources. The data collection technique is to conduct interviews, observations and document studies. Data analysis is carried out with techniques, namely data reduction, data presentation and conclusion drawing. Based on the research findings and analysis carried out, the results show that the activities of fostering and raising intelligence networks are still lacking so that conflict prevention between martial arts organizations is not optimal. Therefore, it requires the support of management elements so that information can be processed by utilizing information according to the needs of the leadership in making decisions to prevent social conflicts. Overcoming social conflicts between martial arts organizations is carried out by all functions of the Karanganyar Police ranks in an integrated manner. Furthermore, a discussion is carried out, so that the author can conclude that social conflict prevention by Karanganyar Police is carried out through the synergy of related agencies through preemptive, preventive and repressive approaches. Optimizing the intelligence network to prevent conflicts between martial arts mass organizations can be effective through optimizing management elements and utilizing intelligence networks from each martial arts organizations. For this reason, the author makes the first suggestion is to propose to the leadership to improve the human resources of intelligence unit members in early detection and expand the intelligence network from various martial arts organizations. Second, it is necessary to map the locations that are of concern and prone to conflict.